CONSIDERATIONS ON CONTACTLESS MEASUREMENTS IN HYDROGEOLOGY USING VERY LOW FREQUENCY ELECTROMAGNETIC TECHNIQUES - Tudor BURLAN-ROTAR (Fiabilitate şi Durabilitate, 2017)
Studies of groundwater consist in data acquisition, their processing and interpretation. In areas of interest hydrogeological is assumed that there is a network of wells drilled. This network provides a first in the hydrogeological information. Electromagnetic (EM) mapping through the use of such areas, using data obtained from existing network of wells drilled, calibration and confirmation. Measurements using the EM can highlight the existence of several layers with different characteristics: clay, limestone, sand, etc. Studies of groundwater interpretation are used for developing a regional hydrogeologic model. The application of electromagnetic techniques for measuring soil resistivity or conductivity has been known for a long time. Conductivity is preferable in inductive techniques, as instrumentation readings are generally directly proportional to conductivity and inversely proportional to resistivity. The operating principle of this method is: a Tx coil transmitter, supplied with alternating current at an audio frequency, is placed on the ground. An Rx coil receiver is located at a short distance, s, away from the Tx coil. The magnetic field varies in time and the Tx coil induces very small currents in the ground. These currents generate a secondary magnetic field, Hs, which is sensed by the Rx receiver coil, together, with primary magnetic field Hp. The ratio of the secondary field, Hs, to the primary magnetic field, Hp, (Hs/Hp) is directly proportional to terrain conductivity. Measuring this ratio, it is possible to construct a device which measures the terrain conductivity by contactless, direct-reading electromagnetic technique (linear meter). This technique for measuring conductivity by electromagnetic induction, using Very Low Frequency (VLF), is a non-intrusive, non-destructive sampling method. The measurements can be done quickly and are not expensive. The Electromagnetic induction technology was originally developed for the mining industry, and has been used in mineral, oil, and gas exploration, and archaeology. In these applications, differences in conductivity of subsurface layers of rock or soil may indicate stratified layers or voids that could be of interest.